Efficacy of bismuth added to standard triple therapy as the first‐line eradication regimen for Helicobacter pylori infection. Issue 3 (1st March 2021) - Kim, Yeon‐Ji; Chung, Woo Chul; Kim, Dae Bum
Abstract: Background: Addressing the increasing antibiotic resistance, including clarithromycin resistance, which affects Helicobacter pylori eradication therapy, is a challenge for clinicians. The objective of this study was to determine the efficacy of bismuth added to standard triple therapy as a first‐line treatment regimen for Helicobacter pylori infection. The secondary outcome was the treatment efficacy for clarithromycin‐resistant strains. Material and Methods: A prospective study was undertaken from January to December 2019. A total of 107 patients with Helicobacter pylori infection were enrolled and received Helicobacter pylori eradication therapy with bismuth added to standard triple therapy for 14 days. We also evaluated the clarithromycin resistance rate by dual‐priming oligonucleotide‐based multiplex PCR and treatment efficacy. Results: A total of 104 patients completed standard triple therapy with bismuth added for Helicobacter pylori eradication. The eradication rates in the intention to treat and per‐protocol analyses were 87.9% and 90.4%, respectively. The frequency of clarithromycin resistance was 33.6% (35/104), and the eradication rate was 77.1% in resistant strains (27/35). Conclusion: Bismuth added to standard triple therapy could be acceptable as a first‐line treatment regimen for Helicobacter pylori eradication in patients with clarithromycin‐resistant strains. In particular, in areas with high clarithromycin tolerance, it is advisable to consider bismuth add‐on therapy as the first‐line treatment regimen.